Clinical Characteristics and Current Therapies for Inherited Retinal Degenerations - Sahel, José-Alain (Cold Spring Harb Perspect Med, 2015)
Inherited retinal degenerations (IRDs) encompass a large group of clinically and genetically heterogeneous diseases that affect approximately 1 in 3000 people (>2 million people worldwide) (Bessant DA, Ali RR, Bhattacharya SS. 2001. Molecular genetics and prospects for therapy of the inherited retinal dystrophies. Curr Opin Genet Dev 11: 307–316.). IRDs may be inherited as Mendelian traits or through mitochondrial DNA, and may affect the entire retina (e.g., rod–cone dystrophy, also known as retinitis pigmentosa, cone dystrophy, cone–rod dystrophy, choroideremia, Usher syndrome, and Bardet-Bidel syndrome) or be restricted to the macula (e.g., Stargardt disease, Best disease, and Sorsby fundus dystrophy), ultimately leading to blindness. IRDs are a major cause of severe vision loss, with profound impact on patients and society. Although IRDs remain untreatable today, significant progress toward therapeutic strategies for IRDs has marked the past two decades. This progress has been based on better understanding of the pathophysiological pathways of these diseases and on technological advances.